(untitled) - Childs, James M.; (1939-...) (U.S.A., 2008)
Peace is not merely a social or political but also, at heart, a religious and theological reality with personal, familial, societal, and global dimensions. In the spirit and style of Paul Tillich, theologian and ethicist James M. Childs, Jr. here asks the most basic questions about the meaning of and ways to peace. He argues that for Christians, peace poses particular problems because of the permanence of conflict and violence amid the assurance that God and Christ are at work creating peace. Uncertainty, ambiguity, struggle, debate, and tragedy are not avoidable. Christian discipleship and peacemaking. Childs argues, are to be lived in and not despite them. His insightful, accessible, honest scoping of the complex way of peace for Christians brings a welcome view of the personal imperative and social prospects that lie within the gritty redemption wrought by the cross and resurrection.
Keywords: Peace -- Religious aspects -- Christianity